Achieving remarkable mechanochromism and white-light emission with thermally activated delayed fluorescence through the molecular heredity principle - Xu, Bingjia (Royal Society of Chemistry, 2016)

(untitled) (Chem Sci)
Achieving high contrast mechanochromism (Δλ(em,max) > 100 nm) and white-light emission under mild conditions from a single compound with a simple structure is a great challenge. Herein, we report a novel dual-emissive compound, namely SCP, with an asymmetric molecular structure that fully inherits the photophysical properties of the parent molecules SC(2) and SP(2). SCP shows high contrast, linearly tunable mechanochromism and bright white-light emission arising from a combination of traditional fluorescence and thermally activated delayed fluorescence (TADF). The origin of the dual-emission for SCP was demonstrated based on the analysis of the white-emitting single crystals. In addition, a mechanism of luminochromism for SCP driven by the application of mechanical force is proposed. These observations present a rational design strategy for the development of high performance multi-functional materials for white-light emission.